2019
DOI: 10.1002/ijc.32502
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of subclonal evolution by temporal mutation profiling in chronic lymphocytic leukemia patients treated with ibrutinib

Abstract: The Bruton's tyrosine kinase (BTK) inhibitor ibrutinib is inducing durable responses in chronic lymphocytic leukemia (CLL) patients with refractory/relapsed disease or with TP53 defect, with BTK and phospholipase C gamma 2 (PLCG2) mutations representing the predominant mechanisms conferring secondary ibrutinib resistance. To understand the landscape of genomic changes and the dynamics of subclonal architecture associated with ibrutinib treatment, an ultra‐deep next‐generation sequencing analysis of 30 recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…Secondary resistance to BTK inhibitors is far better characterized in CLL, where it can be manifested as a Richter transformation during the first year of therapy or as progressive CLL [62,78,[84][85][86]. It was shown that CLL cells under ibrutinib pressure are prone to clonal shifts as determined by whole-exome sequencing studies [87,88]. So far, complex karyotype, 17p deletion and BCL6 abnormalities were shown to be risk factors for acquired secondary resistance [84,89].…”
Section: Resistance Mechanisms and Clinical Implicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Secondary resistance to BTK inhibitors is far better characterized in CLL, where it can be manifested as a Richter transformation during the first year of therapy or as progressive CLL [62,78,[84][85][86]. It was shown that CLL cells under ibrutinib pressure are prone to clonal shifts as determined by whole-exome sequencing studies [87,88]. So far, complex karyotype, 17p deletion and BCL6 abnormalities were shown to be risk factors for acquired secondary resistance [84,89].…”
Section: Resistance Mechanisms and Clinical Implicationsmentioning
confidence: 99%
“…So far, complex karyotype, 17p deletion and BCL6 abnormalities were shown to be risk factors for acquired secondary resistance [84,89]. Whole-exome sequencing analysis of patients with late relapses showed acquired mutations in BTK at the binding site of ibrutinib (C481) with a cysteine to serine mutation, and PLCγ2, the kinase immediately downstream of BTK, where multiple activating mutations were identified [87,88,90].…”
Section: Resistance Mechanisms and Clinical Implicationsmentioning
confidence: 99%
See 3 more Smart Citations